High resolution three‐dimensional imaging and measurement of lung, heart, liver, and diaphragmatic development in the fetal rat based on micro‐computed tomography (micro‐CT). Issue 4 (2nd December 2020) - Markel, Moritz; Ginzel, Marco; Peukert, Nicole; Schneider, Hartmut; Haak, Rainer; Mayer, Steffi; Suttkus, Anne; Lacher, Martin; Kluth, Dietrich; Gosemann, Jan‐Hendrik
Abstract: Understanding of normal fetal organ development is crucial for the evaluation of the pathogenesis of congenital anomalies. Various techniques have been used to generate imaging of fetal rat organogenesis, such as histological dissection with 3‐dimensional reconstruction and scanning electron microscopy. However, these techniques did not imply quantitative measurements of developing organs (volumes, surface areas of organs). Furthermore, a partial or total destruction of the embryos prior to analysis was inevitable. Recently, micro‐computed tomography (micro‐CT) has been established as a novel tool to investigate embryonic development in non‐dissected embryos of rodents. In this study, we used the micro‐CT technique to generate 4D datasets of rat embryos aged between embryonic day 15–22 and newborns. Lungs, hearts, diaphragms, and livers were digitally segmented in order to measure organ volumes and analyze organ development as well as generate high‐resolution 3D images. These data provide objective values compiling a 4D atlas of pulmonary, cardiac, diaphragmatic, and hepatic development in the fetal rat. Abstract : Understanding of normal fetal organ development is crucial for the evaluation of the pathogenesis of congenital anomalies. Various techniques have been used to generate imaging of fetal rat organogenesis, such as histological dissection with 3‐dimensional reconstruction and scanning electron microscopy. However, these techniques did not imply quantitative measurements of developing organs (volumes, surface areas of organs). Furthermore, a partial or total destruction of the embryos prior to analysis was inevitable. Recently, micro‐computed tomography (micro‐CT) has been established as a novel tool to investigate embryonic development in non‐dissected embryos of rodents. In this study, we used the micro‐CT technique to generate 4D datasets of rat embryos aged between embryonic day 15 to 22 and newborns. Lungs, hearts, diaphragms and livers were digitally segmented in order to measure organ volumes and analyze organ development as well as generate high‐resolution 3D images. These data provide objective values compiling a 4D atlas of pulmonary, cardiac, diaphragmatic and hepatic development in the fetal rat.